2006
DOI: 10.2495/etox060231
|View full text |Cite
|
Sign up to set email alerts
|

Set-up of a dynamic in vitro exposure device for the study of indoor air pollutant effects on human derived cells

Abstract: Exposure to air pollutants such as volatile organic chemicals (VOCs) is recognized as a potential cause of allergies, asthma, mucous irritation, headaches and tiredness and may substantially contribute to the increase of cancer incidence in the population. Their presence is not limited to urban and workplace environment but in homes, offices, schools, and hospitals at concentrations often much higher than outdoors. As the number of chemical products created is still increasing, the study of the toxic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The air-liquid system was first developed at the Fraunhofer Institute for Toxicology and Experimental Medicine (ITEM) in Hannover (Germany) to investigate the toxicological effects of tobacco smoke [Aufderheide and Mohr, 2000;Ritter et al, 2001;Aufderheide et al, 2002Aufderheide et al, , 2003Knebel et al, 2002;Wolz et al, 2002;Aufderheide, 2008]. The Vitrocell 1 system has recently been used in several scientific studies and has emerged as a useful instrument for in vitro investigation of VOC and particles [Diabate et al, 2002;Pariselli et al, 2006Pariselli et al, , 2009Seagrave et al, 2007;Paur et al, 2008;Gminski et al, 2010]. Although the Vitrocell 1 system does not reflect the situation in the human respiratory tract, it does provide a useful instrument for estimation of the biological effects in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…The air-liquid system was first developed at the Fraunhofer Institute for Toxicology and Experimental Medicine (ITEM) in Hannover (Germany) to investigate the toxicological effects of tobacco smoke [Aufderheide and Mohr, 2000;Ritter et al, 2001;Aufderheide et al, 2002Aufderheide et al, , 2003Knebel et al, 2002;Wolz et al, 2002;Aufderheide, 2008]. The Vitrocell 1 system has recently been used in several scientific studies and has emerged as a useful instrument for in vitro investigation of VOC and particles [Diabate et al, 2002;Pariselli et al, 2006Pariselli et al, , 2009Seagrave et al, 2007;Paur et al, 2008;Gminski et al, 2010]. Although the Vitrocell 1 system does not reflect the situation in the human respiratory tract, it does provide a useful instrument for estimation of the biological effects in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an absence of secretion of IL‐6 and IL‐8 in A549 cells exposed to VOCs ( m ‐xylene, styrene, and chlorobenzene) with similar concentrations to those used in our study was also observed (Fischäder, Röder‐Stolinski, Wichmann, Nieber, & Lehmann, 2008). However, Pariselli et al have measured significant extracellular IL‐8 secretion after A549 cells acute exposure to 0.2 ppm of benzene or toluene (Pariselli et al 2009; Pariselli, Sacco, & Rembges, 2006). In our case, several hypotheses can be advanced to explain the absence of significant secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Since McCarty and Mackay’s proposal of the importance of critical body residue in environmental exposure, body burden modeling has been gaining momentum in environmental studies. In pharmacokinetic studies, cellular concentration has also been monitored and modeled to guide anticancer drug dosage application, to explain toxicological effects of antifungal agents, and to determine cryoprotection ability for mouse zygotes . With regard to in vitro air exposure studies, the concept of chemical distribution among different matrices according to their physicochemical properties has been overlooked until the rebirth of the use of the hanging drop air exposure system . With the aid of mass balance calculations, we were able to present, for the first time, the cellular EC 50 for toluene, ethylbenzene, and xylenes at 1 h of HD air exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailability determines the fraction of the toxicant that enters the cells and results in subsequent toxicity. Previous studies on air exposure of in vitro systems ,, have focused on achieving a direct air–cell contact to avoid the “media barrier effect” and have focused less on quantitative exposure concentrations. In a sealed environment, compounds will distribute themselves until they reach equilibrium according to their physicochemical properties .…”
Section: Discussionmentioning
confidence: 99%